2020
DOI: 10.1108/prt-03-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of ablative behavior of silicone resin coated carbon fabric

Abstract: Purpose The purpose of this paper is to study the ablative behavior of the silicone resin-coated carbon fabric (coated fabric) that will swell significantly during ablation. Design/methodology/approach The ablation experiments of three coated fabrics were conducted by quartz lamp radiant. Based on the experimental analysis, a numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…13 Another effective approach to simulate the 3D aerogel and to describe the heat transfer mechanism is FE method which serves widely in the thermal insulation field. [14][15][16] For instance, Bi et al 17 and Latre ´et al 18 separately developed ordered geometric models to calculate the thermal conductivity of silica aerogel by finite volume method, and the corresponding results were validated to be identical with available experimental data. In addition, regular models revealed that the predictions of the thermal conductivity were reliable and needed less computational resources than MD approaches.…”
Section: Introductionmentioning
confidence: 99%
“…13 Another effective approach to simulate the 3D aerogel and to describe the heat transfer mechanism is FE method which serves widely in the thermal insulation field. [14][15][16] For instance, Bi et al 17 and Latre ´et al 18 separately developed ordered geometric models to calculate the thermal conductivity of silica aerogel by finite volume method, and the corresponding results were validated to be identical with available experimental data. In addition, regular models revealed that the predictions of the thermal conductivity were reliable and needed less computational resources than MD approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work, the silicone resin was pyrolyzed during the ablation process, whereas the carbon fiber yarn was not. Based on the ablation mechanism of silicone resin-coated carbon fabrics, a numerical model of heat transfer through silicon resin-coated carbon fiber fabrics during ablation has been established, and which was validated by quartz lamp ablation test (Zheng et al , 2020). However, to improve the thermal protective property, this ablation model has been used to optimize the structural parameters of carbon fiber fabric by Zhang et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…FEM is also used in the textile industry, as well as in analyzing the heat transfer of the fabrics, which has exposed the sample's thermal properties (thermal resistance or conductivity), even in the extreme environments. [32][33][34] However, no literature exists on the use of FEM in studying the heat transfer caused by the ring/traveler friction during ring spinning.…”
mentioning
confidence: 99%